Meta Analisis Efektivitas Pelatihan Online dalam Meningkatkan Kompetensi Pedagogik Guru - Rochmah, Luthfi Maulida; Narmayani, Narmayani; Muzekki, Taufikur Rohman; Sobri, Ahmad Yusuf; Ubaidillah, Aan Fardani (Universitas Negeri Malang, 2024)
Abstract : This study aims to determine the effectiveness of online training for teachers in improving pedagogical potential. The method in this study uses meta-analysis which is conducted by reviewing research results relevant to the research variables from various research articles. The purpose of meta-analysis is to obtain more valid and reliable results by synthesizing the results of many different studies conducted. By conducting research on articles published in national journals related to Training and Development in improving teacher pedagogics. Data was collected by searching electronic journals and using the keywords